Processos de verificação e validação da amplificação em crianças com deficiência auditiva: índice de inteligibilidade de fala - SII e comportamento auditivo - Figueiredo, Renata de Souza Lima (2013)
Objective: to establish the relationship between audibility for speech sounds, audiological characteristics and auditory behavioral responses in infants and children under three years of age with sensorineural hearing loss. Method: 41 children aged between 4 and 80 months participated in the study. Seventy-eight ears were analyzed. Auditory thresholds at 250, 500, 1000, 2000 and 4000Hz were considered and values of speech intelligibility index (SII) for the input signals 55, 65 and 75dB SPL were obtained in the Verifit®Audioscan hearing aid analyzer. Three hundred and twelve SII values were obtained. To study the relationship between audibility and auditory behavioral responses, 8 children aged between 11 and 28 months were selected. Auditory response for speech stimulus was observed (the Ling six and four onomatopoeias), before and after the stimuli familiarization activity, controlled by a decibel meter at different distances between evaluator and hearing aid microphone. Other variables were considered for auditory response quality analysis, besides SII values, when identified discrepancy between the expected and the observed behavior in each case. Results: the hearing thresholds have been classified into five groups as homogeneous audiological characteristics (degree and audiometric configuration) and heterogeneous among themselves. Three ranges of SII values were determined from within the groups. The range of 36 to 55% was the most affected by input signal intensity changes. Equations for classification of hearing loss as groups and equations for determination of adjusted SII values were established. In the 8-case study, two children with audibility expressed by SII 65 values lower than 20% did not provide answers for longer distances. In all cases, changes were observed in quality of post-familiarization-activity auditory behavior response. Complex factors such as otitis media, inconsistency of hearing aid use and hearing loss progression were present in some cases and seem to have influenced the quality of auditory behavior observed. Conclusions: SII is an objective measure that allows for amplification adequacy assessment of different hearing loss characteristics, as well as determination of hearing capacity. SII has a stronger correlation with the dynamic relationship between the degree and configuration of hearing loss, when compared to the relationship with the degree of hearing loss alone. Therefore a new classification of hearing loss by groups was established. Hearing losses Gr4 with SII values between 36 to 55% are most affected when the input signal intensity or the distance between speaker and the hearing aid microphone changes. The process of amplification validation in infants with systematic auditory behavior evaluation through familiarization stimuli tests showed that children of up to three years need to be familiar with the stimuli in order to trigger observable auditory responses, thus ensuring results compatible with auditory capacity. Cases classified with hearing loss group Gr4 showed changes in auditory response quality at greater distances. Complex factors affect the quality of auditory behavior responses observed